Oomycetes species associated with soybean in Buenos Aires Province (Argentina) - Grijalba, Pablo E. (2021)
Soybean damping of and root and stem rot are mainly caused by soil oomycetes and they can cause severe seedling stand reductions. Between 2013 and 2016, soybean production areas were sur veyed in diferent localities of the north (NBA) and southeast (SEBA) of Buenos Aires Province. Plant, soil and post harvested grain samples were obtained, brought to the laboratory and treated by multiple techniques. The isolates recovered were identifed using both morphological and molecular characters. As regards seedlings and soil, 68 Phytophthora iso lates were recovered from NBA and 124 from SEBA, all of which were classifed as Ph. sojae. Also 181 Pythium isolates were recovered from NBA and 102 from SEBA, belonging to nine Pythium species and three Phytophytium species; and four Pythium species respectively. In both cases P. ultimum and P. irregu lare were prevalent. With respect to grain samples, a total of 40 Pythium isolates were recovered, belong ing to seven species of Pythium and one species of Phytopythium. The species most frequently recovered were Phy. vexans and P. acanthicum. Pathogenicity was evaluated with representative isolates of each of the 21 species on soybean cv. Harosoy. P. ultimum sensu lato, P. irregulare, P. sylvaticum, P. aphani dermatum and P. paroecandrum were highly patho genic on soybean seedlings, whereas P. acanthicun, P. nunn and P. periplocum were non-pathogenic on soybean seedlings. This study provides a comparative characterization of oomycete species associated with soybean and provides a basis for disease management and breeding programs in Argentina.